Inducing controlled cell cycle arrest and re-entry during asexual proliferation of Plasmodium falciparum malaria parasites. Issue 1 (December 2018) - van Biljon, Riëtte; Niemand, Jandeli; van Wyk, Roelof; Clark, Katherine; Verlinden, Bianca; Abrie, Clarissa; von Grüning, Hilde; Smidt, Werner; Smit, Annél; Reader, Janette; Painter, Heather; Llinás, Manuel; et al.
Abstract The life cycle of the malaria parasitePlasmodium falciparum is tightly regulated, oscillating between stages of intense proliferation and quiescence. Cyclic 48-hour asexual replication ofPlasmodium is markedly different from cell division in higher eukaryotes, and mechanistically poorly understood. Here, we report tight synchronisation of malaria parasites during the early phases of the cell cycle by exposure to DL-α-difluoromethylornithine (DFMO), which results in the depletion of polyamines. This induces an inescapable cell cycle arrest in G1 ( 15 hours post-invasion) by blocking G1 /S transition. Cell cycle-arrested parasites enter a quiescent G0 -like state but, upon addition of exogenous polyamines, re-initiate their cell cycle. This ability to halt malaria parasites at a specific point in their cell cycle, and to subsequently trigger re-entry into the cell cycle, provides a valuable framework to investigate cell cycle regulation in these parasites. We subsequently used gene expression analyses to show that re-entry into the cell cycle involves expression of Ca2+ -sensitive (cdpk4 andpk2) and mitotic kinases (nima andark2), with deregulation of the pre-replicative complex associated with expression ofpk2 . Changes in gene expression could be driven through transcription factors MYB1 and two ApiAP2 family members. This new approach to parasite synchronisation therefore expands our currently limited toolkit to investigate cell cycle regulation in malaria parasites.